2016
DOI: 10.1002/cdq.12073
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well‐Being and Career Indecision in Emerging Adulthood: The Moderating Role of Hardiness

Abstract: This study investigated the moderating role of hardiness in the relationship between psychological well-being (PWB) and career indecision in 131 never-employed Italian emerging adults. Cluster analytic methods produced high and low hardiness profiles. A structural equation modeling analysis underscored the importance of hardiness for moderating the negative association between PWB and career indecision. Specifically, findings revealed that being hardy is a crucial relevant personal resource in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
2
17
0
1
Order By: Relevance
“…Higher scores on any scale indicate greater indices of happiness and psychological well-being. PWB Scales showed Cronbach’s α values ranging from 0.60 to 0.70 [ 76 ], which appears to be a sufficient level of internal consistency based on the fact that each subscale comprised only three items.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores on any scale indicate greater indices of happiness and psychological well-being. PWB Scales showed Cronbach’s α values ranging from 0.60 to 0.70 [ 76 ], which appears to be a sufficient level of internal consistency based on the fact that each subscale comprised only three items.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, our theoretical background ( Gati et al, 1996 ; Gati & Tal, 2008 ) suggests taking into account non-cognitive aspects, such as eudaimonic psychological well-being (PWB), a multifaceted concept referring to the possibility of growing and reaching fulfillment in several domains of life, including career and work ( Ryff & Singer, 2008 ; Ryff, 2014 ). PWB and LoR were shown to be negatively related to each other ( Albion & Fogarty, 2002 ; Multon, Wood, Heppner, & Gysbers, 2007 ; Viola, Musso, Inguglia, & Lo Coco, 2016 ). Furthermore, PWB was also found to be positively associated with SWSE (e.g., Bucki et al, 2015 ).…”
Section: Psychological Well-being Lor and Swsementioning
confidence: 97%
“…Research has shown that SWB is associated with career indecision, difficulties in career decisionmaking, and career decision self-efficacy (Bacanlı, 2016;Uthayakumar et al, 2010). Career distress (Günay & Çelik, 2019) and career indecision (Viola et al, 2016) have been found to negatively affect PWB. In addition, conscious mindfulness exercises (Schutte & Malouff, 2011), which are known to be highly associated with SWB, are known to have beneficial effects for individuals including reducing anxiety during their career choices, improving problem solving skills, and enabling them to have less negative career thoughts (Galles et al, 2019).…”
Section: Psychological Wellbeing (Pwb) and Subjective Wellbeing (Swb)mentioning
confidence: 99%